Development of a simulation tool coupling hydrodynamics and unsteady aerodynamics to study Floating Wind Turbines - Vincent, Leroy; Gilloteaux, Jean-Christophe; Philippe, Maxime; Babarit, Aurélien; Ferrant, Pierre (Volume 10: Ocean Renewable Energy, 2017)
International audience Depending on the environmental conditions, floating Horizontal Axis Wind Turbines (FHAWTs) may have a very unsteady behaviour. The wind inflow is unsteady and fluctuating in space and time. The floating platform has six Degrees of Freedom (DoFs) of movement. The aerodynamics of the rotor is subjected to many unsteady phenomena: dynamic inflow, stall, tower shadow and rotor/wake interactions. State-of-the-art aerodynamic models used for the design of wind turbines may not be accurate enough to model such systems at sea. For HAWTs, methods such as Blade Element Momentum (BEM) [1] have been widely used and validated for bottom fixed turbines. However, the motions of a floating system induce unsteady phenomena and interactions with its wake that are not accounted for in BEM codes [2]. Several research projects such as the OC3 [3], OC4 [4] and OC5 [5] projects focus on the simulation of FHAWTs. To study the seakeeping of Floating Offshore Wind Turbines (FOWTs), it has been chosen to couple an unsteady free vortex wake aerodynamic solver (CACTUS) to a seakeeping code (InWave [6]). The free vortex wake theory assumes a potential flow but inherently models rotor/wake interactions and skewed rotor configurations. It shows a good compromise between accuracy and computational time. A first code-to-code validation has been done with results from FAST [7]on the FHAWT OC3 test case [3] considering the NREL 5MW wind turbine on the OC3Hywind SPAR platform. The code-to-code validation includes hydrodynamics, moorings and control (in torque and blade pitch). It shows good agreement between the two codes for small amplitude motions, discrepancies arise for rougher sea conditions due to differences in the used aerodynamic models.